Children of parents with a history of depression: The impact of a preventive intervention on youth social problems through reductions in internalizing problems. (12th December 2017) - Breslend, Nicole Lafko; Parent, Justin; Forehand, Rex; Peisch, Virginia; Compas, Bruce E.
Abstract: The current investigation examined if changes in youth internalizing problems as a result of a family group cognitive behavioral (FGCB) preventive intervention for families with a parent with a history of depression had a cascade effect on youth social problems over 24 months and the bidirectional nature of these effects. One hundred eighty families with a parent with a history of major depressive disorder ( M age = 41.96; 88.9% mothers) and a youth age 9 to 15 years (49.4% females; M age = 11.46) participated. Findings from a panel model indicated that, compared to a minimum intervention condition, the FGCB intervention significantly reduced youth internalizing problems at 12 months that in turn were associated with lower levels of social problems at 18 months. Similarly, the FGCB intervention reduced internalizing problems at 18 months, which were associated with fewer social problems at 24 months. Changes in social problems were not related to reductions in subsequent internalizing problems. The findings suggest that reductions in youth internalizing problems can lead to lower levels of social problems. Youth social problems are difficult to change; therefore, targeting internalizing problems may be an effective way to reduce the social problems of children of parents with a history of depression.